Equitable Estoppel - Kamarudin, Abdul Rani; Ahmad, Muhamad Hassan (Sweet & Maxwell@ Thomson Reuters, 2022)
Estoppel is a principle of justice and equity. When a person has by his words or conduct led another person to believe in a particular state of affair to then alter his position to his detriment, the person making the representation cannot be allowed to go back on it when it is unjust or inequitable to do so.